Role of Green Supply Chain Management Strategies in Sustainability: Evidence form Manufacturing Industry of Thailand - Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
The study is motivated to estimate role of supply chain management strategies in environmental sustainability. Manufacturing companies of Thailand were selected for the study due to their diverse effect on he environment. Further, role of supply chain management strategies in sustainability has not been thoroughly discussed in developing countries. A questionnaire has been adopted to measure the responses of employees involved in supply chin of manufacturing firm in Bangkok. Structural equation modelling has been adopted to estimate the role of different supply chain management practices in sustainability of environment. The overall results of the study indicate that facility, inventory, information, sourcing, pricing, and transportation have a significant and positive role in sustainability. The interaction of information technology as moderator in the model improves the model strength. Among all of them, inventory management has the highest contribution for sustainability of green initiative in manufacturing enterprises. Effective inventory management tools reduce wastage and protect the environment promptly. Supply chain and inventory procurement managers should develop green supply chain management, remanufacturing, lean production, applications of six-sigma practices, and environmentally friendly package to make sure a safe and protected environment.